Middle-aged and older adults in Aids village: a mixed methods study on talking about death and well-being promotion based on social support theory - Zhang, Lin (Frontiers in Psychology, 2024)
Talking about hope bring well-being (Chan et al., 2019), however, what about talking about death? This study aims to explore the impact of talking about death on the subjective well-being of the rural middle-aged and older adults in China's "Aids village" from five dimensions: the way of talking about death, the attitude towards talking about death, the objects of talking about death with, the frequency of talking about death and the content of the death talk, and investigate whether social support played a mediating role during this process. A field survey and in-depth interviews were conducted in Wen Lou village (a famous Chinese "Aids village"), and valid questionnaires were completed by the HIV/Aids-affected middle-aged and older adults. A series of linear regression analyses were conducted to detect whether the way of talking about death, the attitude towards talking about death, the objects of talking about death with, the frequency of talking about death and the content of the death talk predict the subjective well-being of the HIV/Aids-affected middle-aged and older adults. An empirical test for mediation effect was performed to examine whether social support played a mediating role during the process. It was found that the more frequent the middle-aged and older adults talk about death, the higher level of their subjective well-being is (ΔR 2 = 0.056, 0.05 < p < 0.10), and during which process social support played a mediating role. The author believes that using "talking about death" as a kind of medical intervention, carrying out corresponding life education and death education, and developing a suitable hospice care model, may be a valuable way for the HIV/Aidsaffected middle-aged and older adults in the rural area.